Improvement of accession distinctiveness as an added value to the global worth of the yam (Dioscorea spp) genebank - Girma Tessema, G.; Korie, S.; Dumet, D.; Franco, J. (2012)
Misidentification of accessions is a common problem in genebanks. Along the years, mistakes accumulate and this is particularly true when dealing with a large number of accessions requiring annual regeneration. Human errors such as mislabeling or misreading and material mix up during planting or storage are the main causes for misidentification of accessions. The international collection of yam, maintained at IITA, has accumulated ‘non true to type’ accessions along the years. In the present study, 53 morphological descriptors were used to detect uniformity of individuals within accessions of the yam gene bank collection i.e. agro morphological mismatch between individual plants of the same accession. Based on a similarity matrix, individual pairs with less than 0.90 similarity coefficients, which varies in six descriptors and more, were considered as distinct and mismatched, whereas those that had similarity coefficients greater than or equal to 0.90 were considered as clones from the same parent. Overall, 20.60% of the total 3156 accessions were found not true to type i.e., misidentified individuals. The descriptive analysis shows that morphological traits like distance between lobes, upward folding of leaf along main vein, young stem color, old stem color, leaf shape, leaf density and plant vigor are the most discriminative descriptors for individual identification within accession. Some other traits were also found species specific and they may aid in distinguishing misidentifications between species.